1989
DOI: 10.1007/bf00634460
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of conditioned avoidance responding by trazodone, etoperidone, and MCPP

Abstract: Phenylpiperazines, such as meta-chlorophenylpiperazine (MCPP) a serotonin agonist, have recently been reported to block conditioned avoidance responding (CAR) in the rat, which is an indication of possible antipsychotic utility. Since MCPP is a major metabolite of both antidepressant drugs trazodone (TZ) and etoperidone (ET), both were examined for activity in blocking CAR in a single-trial lever press task in Fisher 344 rats. Both TZ and ET produced dose-related falls in CAR with ED50 values (95% confidence l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Our study demonstrates that trazodone HCl, at 30, 40 and 50 mg/kg i.p., induces catalepsy and antagonizes apomorphine-and dexamphetamine-induced oral stereotypies in rats. Our findings concur with the observations of Martin et al (1989) that trazodone at 9, 18 and 36 mg/kg i.p. doses (expressed as free base) induced catalepsy and antagonized dexamphetamine-induced oral stereotypy in rats.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…Our study demonstrates that trazodone HCl, at 30, 40 and 50 mg/kg i.p., induces catalepsy and antagonizes apomorphine-and dexamphetamine-induced oral stereotypies in rats. Our findings concur with the observations of Martin et al (1989) that trazodone at 9, 18 and 36 mg/kg i.p. doses (expressed as free base) induced catalepsy and antagonized dexamphetamine-induced oral stereotypy in rats.…”
Section: Discussionsupporting
confidence: 96%
“…doses (expressed as free base) induced catalepsy and antagonized dexamphetamine-induced oral stereotypy in rats. Furthermore, since Martin et al (1989) have reported that m-chlorophenylpiperazine (mCPP), a metabolite of trazodone, did not induce catalepsy and antagonized amphetamine stereotypy, it indicates that mCPP does not contribute to these actions of trazodone.…”
Section: Discussionmentioning
confidence: 97%